Advances in Alzheimer's Diagnosis and Therapy: The Implications of Nanotechnology. Issue 10 (October 2017) - Hajipour, Mohammad Javad; Santoso, Michelle R.; Rezaee, Farhad; Aghaverdi, Haniyeh; Mahmoudi, Morteza; Perry, George
Abstract : Alzheimer's disease (AD) is a type of dementia that causes major issues for patients' memory, thinking, and behavior. Despite efforts to advance AD diagnostic and therapeutic tools, AD remains incurable due to its complex and multifactorial nature and lack of effective diagnostics/therapeutics. Nanoparticles (NPs) have demonstrated the potential to overcome the challenges and limitations associated with traditional diagnostics/therapeutics. Nanotechnology is now offering new tools and insights to advance our understanding of AD and eventually may offer new hope to AD patients. Here, we review the key roles of nanotechnologies in the recent literature, in both diagnostic and therapeutic aspects of AD, and discuss how these achievements may improve patient prognosis and quality of life. Trends: Nanotechnology offers a multitude of diagnostic, mechanistic, and therapeutic tools for Alzheimer's disease (AD). Nanobased approaches are already providing new insights to address the pathogenesis of AD. Nanotechnology addresses the multifaceted nature of age-related degeneration, while simplistic linear models of AD, such as amyloid cascade, have failed to address it. Nanoparticles have the utility to address each compartment and phase of the disease in a highly sophisticated manner. Nanotechnology offers new hope for AD where conventional approaches have stalled.